Paurodendron stellatum: a new Permian permineralized herbaceous lycopsid from the Prince Charles Mountains, Antarctica - McLoughlin, Stephen; Drinnan, Andrew; Slater, Ben; Hilton, Jason (Review of Palaeobotany and Palynology, 2015)
Diminutive, silica-permineralized lycopsid axes, from a Guadalupian (Middle Permian) silicified peat in the Bainmedart Coal Measures of East Antarctica are described and assigned to Paurodendron stellatum sp. nov. Axes consist only of primary-growth tissues with a vascular system characterized by an exarch actinostele with 6–20 protoxylem points. Stems have a relatively narrow cortex of thin-walled cells that are commonly degraded, but the root cortex typically contains more robust, thick-walled cells. The stems bear helically inserted, elliptical–rhombic, ligulate microphylls. Roots possess an eccentrically positioned monarch vascular strand. Paurodendron stellatum is one of a very small number of anatomically preserved lycopsid axes described from the Gondwanan Permian and represents the first post-Carboniferous record of this genus. Based on dispersed vegetative remains, megaspores and microspores, herbaceous lycopsids, such as P. stellatum, appear to have been important understorey components of both low- and high-latitude mire forests of the late Palaeozoic. Reconstructing the lost forests of Antarctica: the palaeoecology, anatomy and phylogeny of the iconic Glossopteris flora Exceptional permineralized biotas - windows into the evolution and functional diversity of terrestrial ecosystems through time